Implementation of the Policy on Data Collection and Issuance of Population Administration for Persons with Disabilities in West Bandung Regency, West Java Province - Hendra Trismayadi; Muchlis Hamdi; Andi Pitono; Andi Azikin (International Publisher, 2025)
People with disabilities have the same rights as citizens and are entitled to obtain population administration services. The implementation of the population administration data collection and issuance policy for people with disabilities cannot be separated from problems such as budget constraints, lack of facilities and infrastructure, and limited human resources. The purpose of this study is to examine and analyze the implementation of the population administration data collection and issuance policy for people with disabilities, the inhibiting and supporting factors, and to find an effective implementation model for the population administration data collection and issuance policy for people with disabilities. The research method used by the researcher is descriptive analysis with type his approach is qualitative through interviews, observations, and documentation. Data analysis was carried out use technique triangulation of data to increase the validity of research findings. The results of the study found that the implementation of the population administration data collection and publication policy has a clear target, namely people with disabilities. To achieve the realization of the percentage of targets that have been set, service innovations were found through the development of cooperation with parties or institutions managing people with disabilities with a pick-up service model. In addition, an integrated online service business process was also created through the Online Service Information Registration System (SIDILAN) application. The pick-up service model and online services from the dimensions of productivity and linearity are very effective because in addition to the clear targets and mechanisms, they are also efficient in utilizing resources.